STUDIES ON SEAWEED EXTRACTED ELICITORS AND THEIR ANALYSIS FOR ANTIMI CROBIAL ACTIVITY IN CHICKPEA COTYLEDONS - Bi, Fatima; Iqbal, Seema; Ahmed, Shahnaz; Usmani, Nasim F (Biological Sciences - PJSIR, 2001)
High Molecular Weight Crude Elicitor Preparations HMWCEP obtained from Hypnea musciformis (red algae) were used for elicitation of biologically active secondary metabolites of chickpea (Cicer arietinum) cotyledons.Elicited tissues were extracted with 95% alcohol, concentrated and stored in the fridge. A yellow ppt was collected and fractional extraction of the supernatant provided total alcoholic Ext.I , pet ether Ext.2, chloroform ethyl acetate (3:7) Ext.3 and the residual aqueous Ext.4. Yellow ppt and various extracts were evaluated for their antifungal activity. Ext.2,3 and 4 showed el evated antifungal activity on treatment against some pathogenic and non pathogenic fungi. HPLC method was developed for the separation of complex mixture of induced secondary metabolites of chickpea tissues by the treatment of seaweed elicitors.